A critical study of the contents of books in arithmetic in the primary grades in Thailand - Thumchai, Rawiwan 1931- ([Quezon City s.n.], 1963)
This paper presents an examination and evaluation of the arithmetic textbooks written by Joke Sugandhavanij for use in the primary grades I, II, III and IV of schools in Thailand.
Thesis (M.Ed.)--University of the Philippines
Keywords: Arithmetic -- Study and teaching (Primary); Arithmetic -- Text-books.; Sugandhavanij, Joke. Arithmetic textbook for Grade I-IV.